Antimicrobial Activity of Beluntas (Plucea indica L.) Leaves Extract and Stability of the Activityat Different Salt Concentrations and pHs - Ardiansyah .; Lilis Nuraida; Nuri Andarwulan (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2003)
Beluntas leaves are commonly used as traditional medical herb and fresh vegetables. The aim of the research was to examine the antimicrobial activity of beluntas leaves extracts and the stability of activity in salt and pH condition. Non defatted plar extract had phenol hidroquinon, tanin, alkoloid, and steroid as bioactive compound. The most sensitive bacteria was B. cereus and the most resistant was S. typhi. The MICs of polar extract against, S. typhi, S. aureus, E. coli, P. Fluorescens, B. subtillis, and B. cereus were 3.19, 2.94, 2.66, 2.64, 2.40, and 2.26% respectively. Antimicrobial activity was greater on protoplast of S. typhi sphaeroplast of S. aureus and Bacillus cereus than toward their whole cells, with the highest inhibitionobserved B. cereus protoplast. Addition of salt into the extract increased it's the antimicrobial activity. There was synergism between low pH with bioactive compound from non defatted polar extract. Key words : Beluntas, bioactive compound, MIC, protoplast, sphaeroplast, salt, pH.